Kelayakan Toner Wajah Ekstrak Daun Teh Hijau (Camellia Sinensis) dan Daun Pegagan (Centella Asiatica) untuk Perawatan Kulit Wajah Berjerawat - Mardhiyah, Tarra Ainul; Rosalina, Linda (Lembaga Yasin AlSys, 2023)
Green tea leaf extract facial toner and gotu kola leaves are facial care cosmetics formulated for acne-prone skin types. This cosmetic is made from natural ingredients in the form of green tea leaves and gotu kola leaves which have been dried with a mixture of preservatives and other chemicals. This facial toner functions to moisturize and refresh facial skin, remove excess oil on facial skin and can help close pores on the face. This facial toner contains antioxidants which are great for warding off free radicals that cause acne-prone skin. Purpose: To analyze the facial toner extract of green tea leaves and gotu kola leaves in terms of laboratory tests, organoleptic tests, and organoleptic tests. Method: this research method is an experimental research method. The results of this study based on organoleptic tests showed that the color, aroma, absorption, and preference of the panelists had a fairly high rating level. For laboratory tests, facial toner extracts from green tea leaves and gotu kola leaves had a pH test that was in accordance with the standard pH of facial skin, namely 6.5, which was good for facial skin and the homogeneity test found that all formulations in this toner were homogeneous. In conclusion: facial toner extracted from green tea leaves and gotu kola leaves is suitable for use as a facial toner in terms of laboratory tests (pH test and homogeneity test), organoleptic tests (color, aroma and absorption), and panelist preference test (hedonic).